Framework for Automatic Generation of Hypermedia Applications in Runtime - Soares, Luiz Fernando Gomes; Neto, Carlos de Salles Soares; Junior, José Geraldo de Sousa (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
The automatic generation of hypermedia documents is a subject that still little explored. This paper deals with authoring of dynamic hypermedia documents based on templates. A framework to support the automatic generation of these documents at runtime is proposed and detailed. As an example of use, the framework is instantiated for the automatic development of NCL dynamic applications, also bringing a discussion of the available resources and the native support provided by the Ginga middleware for managing such application types.